2015
DOI: 10.5539/ies.v8n4p60
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Pedagogic Support of Children with Health Limitations

Abstract: The article represented theoretic analysis of the literature on the problem of psychological and pedagogic support of disabled children. It defined the following terms: a successfully adapting disabled child, a model, interaction of specialists, psychological and pedagogic support. The article also determined the key components of a successfully adapting disabled child: personal (includes such features as confidence, adequate self-esteem, and emotional well-being), academic (elementary ideas about himself and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…The fact that students' good health and proper posture is a result of regular physical exercise and a balanced diet cannot be denied (Balkó et al, 2017). According to Ezhovkina and Ryabova (2015) educators and school administrators should create a school environment which builds a positive relationship between children and their movements. As a result of a survey by Balkó et al (2017) it was discovered that 50-60% of students were suggested to carry out a physical exercise on regular basis to correct their bad posture.…”
Section: Healthy Physical Exercises To Keep Students Active Throughou...mentioning
confidence: 99%
“…The fact that students' good health and proper posture is a result of regular physical exercise and a balanced diet cannot be denied (Balkó et al, 2017). According to Ezhovkina and Ryabova (2015) educators and school administrators should create a school environment which builds a positive relationship between children and their movements. As a result of a survey by Balkó et al (2017) it was discovered that 50-60% of students were suggested to carry out a physical exercise on regular basis to correct their bad posture.…”
Section: Healthy Physical Exercises To Keep Students Active Throughou...mentioning
confidence: 99%
“…In the first three years of life the functional basis of mental development is formed and perfected: gnostic abilities, visually-efficient and visually-shaped thinking, memory, attention, etc. [4][5][6][7].…”
Section: A Problem Statementmentioning
confidence: 99%
“…In the first three years of life the functional basis of mental development is formed and perfected: gnostic abilities, visually-efficient and visually-shaped thinking, memory, attention, etc. [4][5][6][7].Early diagnosis of psychomotor and speech development is therefore of particular importance. The insufficiency of motor, mental, speech and emotional development that is detected at an early age adversely affects the further development of the child, leading to difficulties in reading and writing.…”
mentioning
confidence: 99%
“…In order for a child to adapt successfully to the surrounding reality, the main aspect is to identify, justify, and test the pedagogical conditions of functioning of this process. The authors have identified the following conditions of successful implementation of the model of formation of the above-mentioned components of preschoolers' readiness for social and personal orientation at additional education institutions: first, to create a developing environment; second, to organize psychological and pedagogical support to children; and third, to implement the interaction of professionals [35].…”
Section: Literature Reviewmentioning
confidence: 99%